Accounting for wage payments during martial law in Ukraine (Economics and region, 2024)
The article addresses current issues related to the accounting and payment of labor in times of martial law. It emphasizes the multi-level nature of regulatory control over labor payment and highlights job losses due to russia's military aggression against Ukraine. An analysis of the normative definition of "wages" and various approaches to its content has been conducted. The absence of a normative definition for the term "payment for labor" is confirmed, but it is indicated that it is associated with the organization of labor payment and includes wages. The problems associated with income receipt by employers, employees, and the state during martial law are explored. Changes in legislation and new regulatory instruments related to martial law are assessed. The procedure for making payments to employees during martial law in conditionally classified categories is examined (mobilized, volunteers of territorial defense, evacuated or working remotely, involved in community service, those continuing regular duties, temporarily deprived of the opportunity to work without alternative employment). It is proposed to make legislative changes at the state level regarding the peculiarities of terminating employment contracts at the employer's initiative during martial law. The need for employers to take all possible measures to ensure workers' right to receive timely wages during wartime is noted. The importance of accounting and taxation of wages in martial law is determined.
Keywords: accruals; martial law; wages; accounting; sick leave; taxation; vacation pay